CuII Ion Doping Enhances the Water Stability of Luminescent Metal–Organic Framework, Realizing the Detection of Fe3+ and Antibiotics in Aqueous Solutions - Jia, Ruo-Qin; Tan, Geng; Chen, Ying-Jun; Zuo, Lu-Yang; Li, Bo; Wang, Li-Ya (Frontiers in Chemistry, 2022)
Luminescent metal–organic frameworks (LMOFs) have been widely developed in the field of chemical sensing owing to their outstanding photoluminescence performance, high selectivity, anti-interference, high sensitivity, and fast response, and have become one of the research hotspots of emerging functional materials. However, in practical applications, many tests are carried out in the water environment, and fragile water stability greatly limits the application of MOFs in the field. Therefore, it is important to develop a method to enhance the water stability of MOFs. Herein, a new complex [Zn(L)]·CH3CNn (Zn-MOF, H2L = 5-(benzimidazol-1-yl) isophthalic acid) with a superior photophysical property has been synthesized first. Its water stability was highly enhanced by the doping of CuII ions by the one-pot method. In addition, the detection performances of doping material Cu0.1/Zn-MOF for sixteen metal ions and thirteen antibiotics were well studied. It was found that Cu0.1/Zn-MOF displays high sensitivity, fast response, lower detection limit, and long-term stability for the detection of Fe3+, NFT, NFZ, FZD, and TC in the aqueous medium.